T. S. Eliot and Eastern Spirituality - Singh, Ravindra Kumar (Journal for Research in Applied Sciences and Biotechnology, 2023)
Eliot's lifestyle exemplifies his religion. The community that the book provides enables not just Eliot to gratify his own aspirations but also enables others to arrive at similar realizations and locate their place. The work is the culmination of Eliot's lengthy quest for structure and wonder in literature. In spite of Eliot's assertion that the letter in question is neither a manifesto nor a plea to society, its contents suggest otherwise. This work is a reflection of his quest to comprehend the inexplicable as well as his transition from Eastern philosophy, which he explored in The Waste Land and Four Quartets, to Western Christianity, which he adhered to until the very end of his life. The world we live in today is ethically bankrupt, and as a result, the physical takes precedence over the spiritual. The end outcome is a psychological imbalance, a crisis, and decadence. The contemporary surroundings of the waste landers and their unthinking dedication to want, which they believe will fill the gap in their psyches, are the root causes of the spiritual conflict that they face. The poet is looking for psychological coherence. The progression from "The Burial of the Dead" to "What the Thunder Said" alludes to the idea of an individual's eventual salvation from within. The ending of "The Waste Land" ushers in a new way of being in the world. Religion helps the contemporary man find transcendence, inner quiet, and coherence in a time when science, atheism, and sexual liberation are the prevailing worldviews. Religion has the power to ease the suffering of the person and unite his fragmented self into a unified and harmonious whole. Eliot looks to several religious practices for comfort. The idea of travel plays a significant role throughout Eliot's poem. When seen through the lens of an individual's pursuit of psychological and spiritual wholeness, the poem demonstrates forward movement.